Potential of Tebalan Shells from Tuban Beach as Active Material in Perovskite Solar Cells - Roihatur Rohmah; Pelangi Eka Yuwita; Prayoga Dewa Pangestu; Erlangga Dwi Aprila Vibianto (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
One source of environmentally friendly renewable energy that has begun to be widely developed is PSC (Perovskite Solar Cell) made from natural ingredients. PSC is a new breakthrough strategic mineral processing technology as an alternative to silicon in the industry of solar power safety and stability. PSCs are easier to manufacture compared to silicon-based solar cells. The PSC material in this research is perovskite CaTiO3 which is made from the reaction between calcium carbonate (CaCO3) which is obtained from the Tebalan shell powder of Tuban beach and titanium dioxide (TiO2). The method used in this research is substrate preparation, synthesis of Perovskite CaTiO3, making TiO2 paste2, electrolyte solution preparation, counter electrode preparation, fabrication perovskite solar cell (PSC), as well as testing, characterization and data analysis. The tests and characterization that will be carried out are: Crystal structure of powdered materials used in making perovskite solar cells using XRD (X-ray Diffractometer) type X-Pert3 Powder, testing electric current with a potentiometer, and measuring light with a lux meter. The results of XRD testing on the calcined powder showed that the structure of calcium titanate perovskite (CaTiO3) was as much as 68.2%. Meanwhile, the characteristic values ​​of the electrical properties of Tebalan clam shell perovskite solar cells from the lamp light source data obtained show that Vm and Im Daylight lamps have a greater value than warm white lamps and the efficiency value of the solar light source is highest when shown Air Mass 1.5, which is 0.000127%.